The effects of the emotion happy as induced by colors on the performance of grade 1 pupils in addition - M Nael, Michael (Southeast Asia Early Childhood Journal, 2019)
The aim of this study is to determine the effect of the emotion “happy” as induced by colors on the addition performance of grade 1 pupils. The experiment involved the pupils in the experimental group (n=80) were taught addition, using modules developed by the researcher which utilized seductive augmentation of learning materials through colors, the pupils in the control group (n=70) were taught addition using the method in the current math education program which do not utilize emotion-based teaching aids. The study was implemented for 1 week. Pre-test and post-test developed by the researcher based on the math competencies for grade 1 of the Department of Education (DepEd) were administered to the pupils before and after the study and data obtained were statistically analyzed. The study found that Gold, Yellow, Rose, Red and Green were respectively the top five colors that induced happy emotion. Although significant statistical difference was registered between the pre-test and post-tests of the control group (t (70) = -7.04, m = -1.04, sd= 1.23, p = <. 001), the performance of the experimental group registered statistically significant difference over the control group (t (80) = -26.75, m =-. 292, sd=. 99, p = <. 001. This showed that the experimental group had better performance than the control group. Thus, there is statistical basis to claim that the emotion happy as induced by certain colors improved the addition performance of grade 1 pupils.